Enhancing Islamic studies learning through card sort: A case study in Aqīdah Akhlāq and Al-Qur’ān Ḥadīth instruction - Anggraini, Fadhilla Nangroe; Putri, Salsabila Septiana; Mustofa, Triono Ali (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The card sort method is an instructional strategy that promotes active student engagement by encouraging the categorization and organization of key concepts. Widely applied across various subjects, this method has demonstrated its potential to enhance student participation and comprehension. This study investigates the implementation of the card sort method in teaching ‘Aqīdah Akhlāq (Islamic Creed and Morals) for Grade 7 and Al-Qur’ān Ḥadīṡ for Grade 8 at Madrasah Tsanawiyah Negeri (MTsN) 2 Surakarta. The method was chosen for its interactive and collaborative nature, which fosters greater student involvement. Utilizing a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that the card sort method effectively aids Grade 7 students in systematically grasping and classifying moral values and religious doctrines in ‘Aqīdah Akhlāq. Similarly, it supports Grade 8 students in Al-Qur’ān Ḥadīṡ classes by enhancing their ability to identify, connect, and contextualize relevant Qur’anic verses and Hadiths. The study concludes that the card sort method is a valuable pedagogical tool for Islamic Studies instruction, though modifications may be necessary to align with the varying levels of content complexity across different grade levels.